The Relationship Between School Performance Standards And Human Development A Field Study In Public Education Schools In Lattakia Governorate (Journal of Hama University, 2020)
The research aims to study the extent to which total quality management standards have been achieved in the elements of the school educational system, from the viewpoint of principals and teachers of general education schools in Lattakia Governorate. In addition to studying the relationship between the quality standards of the elements of the school educational system and the satisfaction of society, the labor market and various community institutions as an indicator of human development.The research adopted the descriptive analytical method, and the research sample was determined using the Statistical Sample Law, as it was distributed among (281) managers and directors, and (379) teachers, distributed to the educational levels and educational areas using proportional distribution.The results showed that there is a statistically significant relationship between the quality of the elements of the school educational system, and human development, and that the elements of the school educational system most influential in achieving community satisfaction and the labor market (as an indicator of human development) about school performance are monitoring and following up the educational process, the performance of the social counselor, and the school building Evaluation methods, textbook.